Effect of climate change on road traffic accidents in the UAE: a narrative review - Ambanattu, Ewan T.; Umar, Abdurrahman C.; Akolaa, Ethel A.; Sreejith, Anusha; Sreedharan, Jayadevan; Muttappallymyalil, Jayakumary (International Journal Of Community Medicine And Public Health, 2023)
Road traffic accidents (RTA) is a major cause of death and disability all over the world. It is the leading cause of death in children and young adults aged 5-29 years. Worldwide, it is a growing public health concern as, approximately, 1.3 million people die every year due to RTA. It is also taxing on a country’s GDP as at least 3% of the GDP is spent on RTA’s annually. In 2020, there were 3.14 deaths per 100,000 in the UAE and this number increased by 20% in 2021. It also happens to be the second highest cause of death after cardiovascular diseases. There are many factors like speeding, driving under the influence, distracted driving, nonuse of seatbelts etc. which can cause accidents. Weather phenomenon is an overlooked factor which can cause an increase in the number of RTAs. Climate change has resulted in a global increase of temperature and an increase in weird weather phenomenon like increased rainfall, fog, smog, snowfall etc. Very limited studies have been conducted to see the relationship between the two and none have been conducted in the UAE. This review was done based on articles selected from PubMed and SpringerLink, to see whether the results could be applicable in this region. In countries like Saudi Arabia and Pakistan, increased rainfall and fog has resulted in an increase in the number of fatal accidents whereas in the USA, it was observed that the warmer temperatures have resulted in a higher number of fatal accidents. Hence, there is a need to assess the impact of climate change on RTA.